Analisis Evaluasi Pemanfaatan Sumber Daya Air Di Das Batang Arau Kota Padang Menggunakan Program Linier - Putri, Jeffilianti Tri; Sujatmoko, Bambang; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Batang Arau basin consists of seven sub districts, namely Padang Selatan Sub district, Padang Barat Sub district, Padang Timur Sub district, North Padang Sub district, Bungus Teluk Kabung Sub district, Lubuk Begalung sub district, and Lubuk Kilangan sub district. The city of Padang currently developing, consequently changes land use, fearing the potential and volume of water discharge in the Batang Arau basin will experiencing a shortage due to lack of water absorption. Due to limit water resources, an evaluation of the utilization of water resources is conducted using the QM for Windows 5 program. Depenable discharge and water requirements of each sector are the constraint that are input into a linear program. The results of the evaluation of this water utilization analysis obtained 121 industries, 1,219 beds in hotels, 2,199 beds in hospitals, and 470,088 denizen and 1,785 ha of irrigation with three alternative cropping patterns. Of the several alternatives, the biggest profit is obtained in alternative I with a profit of Rp.58,669,796,046.00/year. Based on the evaluation of water utilization analysis, it was found that the condition of the Batang Arau basin until 2017 was not a deficit.Keywords: Water utilization, linear programming, QM For Windows 5